A therapist's guide to adolescent development : supporting teens and young adults in their families and communities - Jayne, Kimberly M.; Purswell, Katherine E. (New York, NY : Routledge, 2025)
"A Therapist's Guide to Adolescent Development is a practical guide to understanding adolescent development and applying developmental knowledge in therapeutic practice. Chapters explore development and therapeutic considerations for specific age ranges in pre-adolescence, early, middle, and late adolescence. The final chapter includes reproducible, age-specific handouts about adolescent development for use by counselors and therapists to educate and collaborate with adolescents and their significant adults, including parents, caregivers, teachers, and mentors. Clinical examples representing diverse clients are provided throughout the book to support culturally sustaining practice and practical application. This unique and meaningful book will benefit any mental health professional or student who wants to integrate developmental knowledge into practice in a way that educates, empowers, and promotes collaboration with adolescents rather than pathologizing them"--
Keywords: Adolescent psychology; Adolescence; PSYCHOLOGY / Psychotherapy / Child & Adolescent; PSYCHOLOGY / Developmental / Adolescent